2021
DOI: 10.1136/jitc-2020-002224
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral OH2, an oncolytic herpes simplex virus 2, in patients with advanced solid tumors: a multicenter, phase I/II clinical trial

Abstract: BackgroundOH2 is a genetically engineered oncolytic herpes simplex virus type 2 designed to selectively amplify in tumor cells and express granulocyte-macrophage colony-stimulating factor to enhance antitumor immune responses. We investigated the safety, tolerability and antitumor activity of OH2 as single agent or in combination with HX008, an anti-programmed cell death protein 1 antibody, in patients with advanced solid tumors.MethodsIn this multicenter, phase I/II trial, we enrolled patients with standard t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 24 publications
0
47
0
Order By: Relevance
“…Zhang et al showed that oHSV therapy led to an increase in tumour-infiltrating CD4 and CD8 T cells and a decrease in Treg and suppressive TAM in a mouse model of pancreatic ductal adenocarcinoma (PDAC). PDAC is a notoriously immune-excluded, "cold" tumour, with a TME comprising immunosuppressive Treg, tumour associated macrophages (TAM), immunosuppressive cytokines and physical barriers to T cell infiltration such as CAFs and a desmoplastic stroma (52). Transcriptome profiling of immune cells following treatment showed enrichment of PD-1, LAG-3 and TIM-3 in the CD8 T cell population, and OX40 and CTLA-4 in the CD4 population (53).…”
Section: Localised Ov and Checkpoint Blockade Combinations -Pre-clinical Studiesmentioning
confidence: 99%
“…Zhang et al showed that oHSV therapy led to an increase in tumour-infiltrating CD4 and CD8 T cells and a decrease in Treg and suppressive TAM in a mouse model of pancreatic ductal adenocarcinoma (PDAC). PDAC is a notoriously immune-excluded, "cold" tumour, with a TME comprising immunosuppressive Treg, tumour associated macrophages (TAM), immunosuppressive cytokines and physical barriers to T cell infiltration such as CAFs and a desmoplastic stroma (52). Transcriptome profiling of immune cells following treatment showed enrichment of PD-1, LAG-3 and TIM-3 in the CD8 T cell population, and OX40 and CTLA-4 in the CD4 population (53).…”
Section: Localised Ov and Checkpoint Blockade Combinations -Pre-clinical Studiesmentioning
confidence: 99%
“…T-VEC is currently in clinical trials for pancreatic cancer, non-melanoma skin cancer, breast cancer, and sarcoma. OH2 , oHSV-2 expressing GM-CSF with a similar structure to that of T-VEC, has entered clinical trials in China for metastatic solid tumors with injectable lesions (NCT04386967) [ 157 ].…”
Section: Armed Ohsvmentioning
confidence: 99%
“…HF10 ( Figure 4 ) was evaluated in a phase II clinical trial in combination with ipilimumab in advanced melanoma with a best overall response (BOR) of 41% [ 72 ]. In a phase I/II clinical trial of OH2 (T-VEC-like oHSV-2) alone or in combination with anti-PD-1 (HX008) in patients with advanced solid tumors with injectable lesions, two of 33 patients taking OH2 alone and two of 12 in the combination-treated group had an immune partial response (iPR) that was durable [ 157 ]. Increases in PD-L1 + cells and CD8 + T cells after OH2 alone were observed in most evaluated patients relative to baseline, irrespective of response [ 157 ].…”
Section: Combination Therapiesmentioning
confidence: 99%
See 2 more Smart Citations